Sonographic Appearance of the Pronator Quadratus Muscle in Healthy Volunteers. (1st January 2014) - Sato, Junko; Ishii, Yoshinori; Noguchi, Hideo; Takeda, Mitsuhiro; Toyabe, Shin-ichi
Abstract : Objectives: The purpose of this study was to investigate the sonographic appearance of the pronator quadratus muscle in healthy volunteers. Methods: We sonographically evaluated 30 healthy volunteers (15 men and 15 women). The maximum thickness of the pronator quadratus in millimeters on the volar side at the cortical level was measured on sagittal and axial sonographic images with the volunteers' hands supinated. On the axial image, we classified each hand according to the sonographic contour of the pronator quadratus. Results: A significant difference in the maximum pronator quadratus thickness between dominant and nondominant hands was shown on each image ( P < .01). A comparison between men and women also showed a significant difference irrespective of image or hand dominance. Approximately 1.5 mm on the sagittal image and 1.4 mm on the axial image seemed to be adequate practical values for detecting pronator quadratus thickening. In terms of the pronator quadratus contour, the convex type appeared in most men in both the dominant and nondominant hands. In women, the convex and concave types appeared often in both the dominant and nondominant hands. Conclusions: The difference in pronator quadratus thickness between dominant and nondominant hands might need to be taken into account during sonographic studies. However, in many cases, the difference seems to be slight and considerably less than the calculated cutoff value in this study. These results might be useful for sonographic comparison of bilateral pronator quadratus muscles in the clinical setting.